2014
DOI: 10.1177/1098214014542100
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Using Developmental Evaluation for Innovating

Abstract: This article contributes to research on evaluation by examining the capacity and contribution of developmental evaluation for innovating. This case study describes the preformative development of an educational program (from conceptualization to pilot implementation) and analyzes the processes of innovation within a developmental evaluation framework. Developmental evaluation enhanced innovation by (a) identifying and infusing data primarily within an informing process toward resolving the uncertainty associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This shift in orientation to embedding evaluation as a part of the innovation itself further advances our understanding of the concept of adaptation in practice . Complexity and systems‐informed approaches like Developmental Evaluation recognize the critical role of learning, adaptive strategy in program development and innovation contexts (Dinca‐Panaitescu, 2020; Lam & Shulha, 2015). Yet, the knowledge, skills, and abilities of program staff to design under conditions of dynamic complexity are often assumed rather than fully articulated in these methods.…”
Section: Design Requirementsmentioning
confidence: 99%
“…This shift in orientation to embedding evaluation as a part of the innovation itself further advances our understanding of the concept of adaptation in practice . Complexity and systems‐informed approaches like Developmental Evaluation recognize the critical role of learning, adaptive strategy in program development and innovation contexts (Dinca‐Panaitescu, 2020; Lam & Shulha, 2015). Yet, the knowledge, skills, and abilities of program staff to design under conditions of dynamic complexity are often assumed rather than fully articulated in these methods.…”
Section: Design Requirementsmentioning
confidence: 99%
“…In our midpoint data, signifi cant conceptual confusion surrounding the diff erence between evaluation and other forms of inquiry was revealed. Distinguishing evaluation from research has been a focus of theorizing in the fi eld of evaluation for some time (e.g., Fain, 2005 ;Fitzpatrick, Sanders, & Worthen, 2004 ;Levin-Rozalis, 2003 ;Patton, 2014 ). Some participants attributed their initial thinking to past experiences where research was viewed as more esoteric and evaluation as a topdown activity that did not easily generate useful fi ndings.…”
Section: Promoting Evaluative Thinkingmentioning
confidence: 99%
“…Patton (2011) notes that the deep knowledge accumulated by an experienced evaluator about the nature of what is likely to work is very useful in helping a development team articulate an initiative's programme theory. Programme theory was used to provide a framework to inform the development of the Assessment Pilot Initiative (Lam & Shulha, 2015). In New Zealand, McKegg, Wehipeihana, Pipi and Thompson (2013) used a developmental evaluation approach to support the implementation of a significant change in focus for He Oranga Poutama.…”
Section: Helping To Articulate the Objectives And Success Measures Ofmentioning
confidence: 99%
“…During the developmental evaluation of the Māori and Pacific Educational Initiative, the evaluators found that instead of an approach of interim and final reports, the needs of the trustees of the philanthropic trust to be kept informed of progress were better met by regular, shorter reports containing quantitative data as it became available . Lam and Shulha (2015) consider that the nature of the data used in the development of a teacher education tool was broader than what is traditionally collected in a summative evaluation, such as data about an initiative's activities or outcomes. For example, the data provided included information from the social science and education literature about the use of technology to assist learning, which provided the development team with new ideas for the initiative.…”
Section: Providing Data As Initial Impacts Emergementioning
confidence: 99%
See 1 more Smart Citation